A Rare Complication of Typhoid Fever: Perforated Gallbladder in Children - Imtiaz Ahmed, Muhammad Akbar, Rooman Qureshi, Iqra Aslam, Ali Hasham, Asma Memon, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gall bladder perforation is a rare complication in the pediatric age group secondary to enteric fever and a definitive diagnosis is necessary to deal with the management. Preoperative diagnosis of gallbladder perforation is challenging and demanding in most cases diagnosed intraoperatively. Our study aims to evaluate the pattern of presentation, investigation, and complication. Methods: A descriptive case series was carried out in our pediatric department of surgery at Liaquat University Hospital Hyderabad Sindh Pakistan from January 2016 to December 2021. Data were analyzed regarding age, clinical presentation, investigation, surgical procedure, site of perforation, complication, and outcome. Results: Eleven patients were managed in five years. The patient's ages ranged from 6 years to 12 years old child of 9.19 years was the mean age of presentation. The fundus and body was the commonest site of perforation and was diagnosed intraoperatively. The presenting feature was fever, abdominal pain with distension, vomiting, constipation, and a sign of peritonism. The gallbladder perforation was managed by cholecystectomy in 10 patients and partial in one due to difficult dissection. In our series, zero mortality, and all eleven patients were symptom-free in the postoperative outpatient department clinic. Conclusion: In Perforated gallbladder patients early and aggressive management improves mortality and morbidity but represents a special diagnostic and surgical challenge. Keywords: Typhoid Fever, Perforated Gallbladder, Acalculous Cholecystitis.